2021
DOI: 10.1007/s42452-021-04289-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen reduction on silver catalysts electrodeposited on various nanocarbon supports

Abstract: In this work, Ag particles were electrodeposited onto nitrogen-doped graphene oxide, graphene, multi-walled carbon nanotube (MWCNT), and Vulcan carbon XC-72R supports by varying the upper potential limit. The surface morphology of the resulting Ag-based catalysts was examined by scanning electron microscopy. The electrochemical oxygen reduction reaction (ORR) was tested in alkaline media employing the rotating disk electrode method. The variation of the upper potential limit influenced the size of silver nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 57 publications
4
16
0
Order By: Relevance
“…We obtained comparable MA values to those reported in the literature. [38,48] For example, in our recent article, where silver was electrodeposited onto four different carbon substrates, the MA values at 0.8 V were similar when compared to the results obtained in this work. [38] Also, the MA values at 0.85 V in a study by Cai et al, where the ORR was tested on Ag catalysts prepared by rapid precipitation-reduction synthesis, were close to those of this work.…”
Section: Cyclic Voltammetry (Cv) Measurementssupporting
confidence: 82%
See 2 more Smart Citations
“…We obtained comparable MA values to those reported in the literature. [38,48] For example, in our recent article, where silver was electrodeposited onto four different carbon substrates, the MA values at 0.8 V were similar when compared to the results obtained in this work. [38] Also, the MA values at 0.85 V in a study by Cai et al, where the ORR was tested on Ag catalysts prepared by rapid precipitation-reduction synthesis, were close to those of this work.…”
Section: Cyclic Voltammetry (Cv) Measurementssupporting
confidence: 82%
“…Similar values of E 1/2 were obtained in other recent works. [21,[36][37][38] The Koutecky-Levich (K-L) equation was used to determine the ORR kinetic parameters. The number of electrons transferred per O 2 molecule (n) was calculated from RDE data using the K-L equation [Eq.…”
Section: Rotating Disc Electrode (Rde) Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We further calculated the theoretical dissolution potentials ( U ) of the alloys to estimate the stability of the catalytic surface under the working conditions. In fact, it has been suggested that the main factor for catalyst degradation is the dissolution of the catalyst in PEMFC. , In AEMFCs, which improve the catalyst stability by lowing the operating potential through the use of alkaline electrolytes, it was also reported that the dissolution of Ag still occurs. , The theoretical dissolution potential ( U ) of the alloys was calculated to estimate the electrochemical stability of the catalytic surface under the working conditions, as given by equation . where U Ag 0 is the dissolution potential of pure Ag under standard conditions and E alloy , E subsurf , and μ Ag are the energies of the alloy surface with a pure Ag skin, the energy of the surface after complete surface layer dissolution, and the chemical potential of the pure bulk Ag, respectively. N surf is the number of surface atoms, and n is the number of electrons transferred during dissolution.…”
mentioning
confidence: 99%
“…45,46 In AEMFCs, which improve the catalyst stability by lowing the operating potential through the use of alkaline electrolytes, it was also reported that the dissolution of Ag still occurs. 33,47 The theoretical dissolution potential (U) of the alloys was calculated to estimate the electrochemical stability of the catalytic surface under the working conditions, 48 as given by equation 11.…”
mentioning
confidence: 99%